Project-Based Effectiveness with Digital Literacy Blended Learning (DLBL) to Improve Cognitive Abilities in Electrochemical Subjects - fitriana, Nurin; Ikawati, Any (Pendidikan Kimia Unimus, 2023)
The purpose of this research is to measure the effectiveness of the Digital Literacy Blended Learning (BLDD) method with a project based learning model in an effort to increase students’ cognitive abilities in the subject of electrochemistry.The research subjects were 30 students who took Engineering Chemistry courses at the Faculty of Engineering, University Wisnuwardhana Malang. The research design was a quasiexperimental version of one group pre-post test only. The instrument uses test and nontest.The test instrument was analyzed using the Kolmogorov-Smirnov technique normality test, the Anova linearity test, and the correlation test using the SPSS 26 program.The non-test instrument with a questionnare using a likert scale was analyzed to calculate Frequency and TCR.The results showed that the normality test was 0,180 with a linear relationship with a p-value (0,428) > 0,05, this indicated that students cognitive abilities increased supported by a correlation test value of 0,382 with a significance level of 0,037. Analysis of the result of the treatment questionnaire shows an average frequency of 4,52 and TCR of 83,64 which indicates that the treatment of this method is very good. The Blended Learning Literacy (BLDD) strategy is very effective in improving students cognitive understanding of electrochemical material.